Phenotypic and molecular characterization of clinically isolated Escherichia coli - Vaishnavi Chetana; Kaur Sukhminderjit; Beutin Lothar; Krueger Ulrike (Wolters Kluwer Medknow Publications, 2010)
All diarrheagenic Escherichia coli carry at least one virulence-related property. Stool samples from 244 patients having acute or persistent diarrhea received after the exclusion of routine enteropathogens were investigated. Purely or predominantly isolated E. coli (n = 100) were subjected to serotyping, of which only 25 were typable. They belonged to 14 different O-serogroups comprising 5 O153, 4 O102, 3 O25, 2 each of O130 and O169, and 1 each of O1, O8, O15, O37, O86, O101, O127, O143, and O160. The typable E. coli isolates along with 5 other untypable isolates were investigated for molecular markers, such as intimin (eae), enterohemolysin (EhlyA), a-hemolysin, heat-labile enterotoxins (LT), heat-stable enterotoxins (STa), verotoxins (VT1 and VT2), invasivity (ial), enteroaggregative E. coli (EAEC) gene (EAGG), and enterotoxin (EAST). Two of the isolates (O153 and O86) were positive for enterohemolysin phenotypically and 5 for β-hemolysin both phenotypically and genotypically. Interestingly, 16.6% of the randomly isolated E. coli were O153, a serogroup common in cattle, and 10% belonged to EAEC pathotype of which two-thirds had the EAST gene, which is quite frequent in these strains. Additionally, there was one strain (O153) that was positive for EAST only. Between the two 0130:H6 strains isolated, one belonged to EAEC serogroup. None of the E. coli isolated were positive for verotoxins, eae, LT1, STa, and ial. Data obtained emphasize the need for additional research into the role of eae gene and other putative factors affecting the virulence of diarrheagenic E. coli in India.